Silibinin Regulates Lipid Metabolism and Differentiation in Functional Human Adipocytes - Barbagallo, Ignazio; Vanella, Luca; Cambria, Maria T.; Tibullo, Daniele; Godos, Justyna; Guarnaccia, Laura; Zappalà, Agata; Galvano, Fabio; Li Volti, Giovanni (Frontiers in Pharmacology, 2016)
Silibinin, a natural plant flavonoid, is the main active constituent found in milk thistle (Silybum marianum). It is known to have hepatoprotective, anti-neoplastic effect and suppresses lipid accumulation in adipocytes. Objective of this study was to investigate the effect of silibinin on adipogenic differentiation and thermogenic capacity of human adipose tissue derived mesenchymal stem cells. Silibinin (10 μM) treatment, either at the beginning or at the end of adipogenic differentiation, resulted in an increase of SIRT-1, PPARα, Pgc-1α and UCPs gene expression. Moreover, silibinin administration resulted in a decrease of PPARγ, FABP4, FAS and MEST/PEG1 gene expression during the differentiation, confirming that this compound is able to reduce fatty acid accumulation and adipocyte size. Our data showed that silibinin regulated adipocyte lipid metabolism, inducing thermogenesis and promoting a brown remodelling in adipocyte. Taken together, our findings suggest that silibinin increases UCPs expression by stimulation of SIRT1, PPARα and Pgc-1α, improved metabolic parameters, decreased lipid mass leading to the formation of functional adipocytes.